Health Beliefs of Nurses in Northern Thailand: A Q-Methodology Study - Marisa Guptarak (2019)
© The Author(s) 2019. Introduction: Northern Thailand has a distinct culture and set of health beliefs. Nurses’ beliefs influence approaches to care affecting health care outcomes. This study explored the content, origin, and sociocultural influences on health beliefs of Northern Thai nurses and how they influence clinical practice and education. Method: Q-methodology was used in this study. Data were collected with interviews using Q-cards, Q-sort distribution board, and a semistructured interview guide. Results: Data were collected from 30 clinical nurses and 30 nurses working in academia. Q-factor analysis produced three factors accounting for 48% of variance: personal experience, Thai and Buddhist beliefs, and contemporary beliefs. Discussion: Participants who felt strongly rooted in their culture and beliefs were homogeneous in recognizing the need for evidence-based practice. Nurses aware of the nature and sources of their beliefs and those of patients are well-placed to balance maintenance of cultural traditions with the need to provide evidence-based practice.